Protrusive maxillomandibular fixation for intracapsular condylar fracture: a report of two cases - Jeong, Yeong Kon; Park, Won-Jong; Park, Il Kyung; Kim, Gi Tae; Choi, Eun Joo (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2017)
Clinical limitations following closed reduction of an intracapsular condylar fracture include a decrease in maximum mouth opening, reduced range of mandibular movements such as protrusion/lateral excursion, and reduced occlusal stability. Anteromedial and inferior displacement of the medial condyle fragment by traction of the lateral pterygoid muscle can induce bone overgrowth due to distraction osteogenesis between the medial and lateral condylar fragments, causing structural changes in the condyle. In addition, when conventional maxillomandibular fixation (MMF) is performed, persistent interdental contact sustains masticatory muscle hyperactivity, leading to a decreased vertical dimension and premature contact of the posterior teeth. To resolve the functional problems of conventional closed reduction, we designed a novel method for closed reduction through protrusive MMF for two weeks. Two patients diagnosed with intracapsular condylar fracture had favorable occlusion after protrusive MMF without premature contact of the posterior teeth. This particular method has two main advantages. First, in the protrusive position, the lateral condylar fragment is moved in the anterior-inferior direction closer to the medial fragment, minimizing bone formation between the two fragments and preventing structural changes. Second, in the protrusive position, posterior disclusion occurs, preventing masticatory muscle hyperactivity and the subsequent gradual decrease in ramus height.